The effect of wavelet transform on OFDM system in modern cellular networks - Mayada Faris Ghanim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The performance of OFDM (Orthogonal Frequency Division Multiplexing) proved that it was an excellent technique for 4G.It provides good spectrum efficiency and it has excellent throughput in different situations. This technique can be improved to be suitable for 5G systems. Wavelet transform has many advantages that make it suitable and efficient approach to replace Fast Fourier Transform (FFT) in conventional OFDM systems. Wavelet transform is employed in modern cellular networks to remove the use of cyclic prefix, which leads to decreasing the bandwidth losses and the power of transmission. Wavelet based OFDM system is designed in order to overcome the drawbacks of OFDM system so that the proposed system is good candidate for next generation of wireless communications.